2019
DOI: 10.1002/adsc.201901184
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanistic Study of the Stereochemical Outcomes of Rhodium‐Catalysed Styrene Aziridinations

Abstract: The stereoselective, rhodium-catalysed aziridination of styrene derivatives with a chiral Nmesyloxycarbamate was found to be highly substrate dependent. A density functional theory (DFT) study is herein reported to elucidate the stereochemical outcome of the aziridination process. Rhodium acetate was initially used as a model catalyst, followed by computational studies conducted with Rh 2 [(S)-nttl] 4 . Both singlet and triplet rhodium nitrene species were identified as intermediates affording concomitant conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 126 publications
1
11
0
Order By: Relevance
“…Alma et al [ 26 ] demonstrated a nitrene radical intermediate in the Co‐porphyrin‐catalyzed aziridination of alkene, which occurs via the stepwise mechanism. Azek et al [ 27 ] elucidated that both singlet and triplet rhodium nitrene species are identified in the evolution of the aziridination process.…”
Section: Introductionmentioning
confidence: 99%
“…Alma et al [ 26 ] demonstrated a nitrene radical intermediate in the Co‐porphyrin‐catalyzed aziridination of alkene, which occurs via the stepwise mechanism. Azek et al [ 27 ] elucidated that both singlet and triplet rhodium nitrene species are identified in the evolution of the aziridination process.…”
Section: Introductionmentioning
confidence: 99%
“…The sulfimidation of thioanisole with singlet Rh-nitrenes 9 and 10 displayed an overall free activation barrier, whereas singlet Rh-nitrene 11 shows 5.0 kcal mol –1 activation free energy (Figure ). The sulfimidation of thioethers is thus an easier process in comparison to rhodium nitrene aziridination and C–H amination reactions, something that is also observed experimentally…”
Section: Resultsmentioning
confidence: 61%
“…Experimental evidence suggests that the rhodium nitrenoid species (L 4 Rh-N­( OMs )­R) might be the reactive intermediate in the amination of thioethers. This is in sharp contrast with what was observed in C–H and CC amination reactions using the same catalytic system . To establish the factors that govern the mechanism (Rh-nitrenoid vs rhodium nitrene), a density functional theory (DFT) study investigating rhodium­(II)-catalyzed thioether amination is reported herein.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations